The complete stories - Kafka, Franz frey50; Glatzer, Nahum Norbert, 1903-; Updike, John (New York : Schocken Books : Distributed by Pantheon Books, 1988)
Portrays a dreamlike world in which parables are even more obscure than the novels.
Before the law -- An imperial message -- Description of a struggle -- Wedding preparation in the country -- The judgment -- The metamorphosis -- In the penal colony -- The village schoolmaster [The giant mole] -- Blumfeld, an elderly bachelor -- The warden of the tomb -- A country doctor -- The hunter Gracchus -- The hunter Gracchus : a fragment -- The great wall of China -- The news of the building of the wall : a fragment -- A report to an Academy -- A report to an Academy : two fragments -- The refusal -- A hunger artist -- Investigations of a dog -- A little woman -- The burrow -- Josephine the singer, or the mouse folk -- Children on a country road -- The trees -- Clothes -- Excursion into the mountains -- Rejection -- The street window -- The tradesman -- Absent-minded window-gazing -- The way home -- Passers-by -- On the tram -- Reflections for gentlemen-jockeys -- The wish to be a red Indian -- Unhappiness -- Bachelor's ill luck -- Unmasking a confidence trickster -- The sudden walk -- Resolutions -- A dream -- Up in the gallery -- A fraticide -- The next village -- A visit to a mine -- Jackals and Arabs -- The bridge -- The bucket rider -- The new advocate -- An old manuscript -- The knock at the manor gate -- Eleven sons -- My neighbor -- A crossbreed [A sport] -- The cares of a family man -- A common confusion -- The truth about Sancho Panza -- The silence of the Sirens -- Prometheus -- The city coat of arms -- Poseidon -- Fellowship -- At night -- The problem of our laws -- The conscription of troops -- The test -- The vulture -- The helmsman -- The top -- A little fable -- Home-coming -- First sorrow -- The departure -- Advocates -- The married couple -- Give it up! -- On parables.
Keywords: Kafka, Franz, -- 1883-1924 -- Translations, English